The impact of nurse leadership education on clinical practice: An integrative review. (9th July 2021) - Page, Ashley; Halcomb, Elizabeth; Sim, Jenny
Abstract: Aim: The aim of this paper is to critically evaluate the literature investigating the impact of nurse leadership education on clinical practice. Background: Effective leadership is vital for high‐quality patient care. Leadership education is designed to support nurses to develop the appropriate skills and behaviors to become clinical leaders. However, to date, the impact of such education on subsequent clinical practice is unclear. Evaluation: An integrative review was conducted. Ten papers were included related to the experiences of nurses undertaking leadership education. Key issue: Analysis of the included papers indicated that leadership education contributed to improving clinical practice in two ways. These two key themes were; impact on the individual and impact on others. Conclusion: While there is a plethora of literature reviewing nurse leadership and clinical practice, there is a gap in understanding how nurse leadership education can contribute to changed practice. Implications for Nursing Management: Nurse managers can use this information to guide future leadership education programs to ensure that they promote positive work environments and high‐quality care that improves clinical outcomes.